Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/app.54428
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mercerization on water conductivity in cotton fabrics and its regulation

Abstract: Mercerization had been widely used in the textile industry because of its simplicity and ability to improve the luster, strength, and dyeing properties of cotton fabrics. However, the water transfer behavior of mercerized cotton fabrics had not been systematically investigated. In this work, cotton fabrics were treated with different concentrations of alkali (130 and 260 g/L) for structural characterization (scanning electron microscopy [SEM], Fourier transform infrared [FTIR]), water absorption (vertical wick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…59 Meanwhile, the coating on the surface of the fabric increased the tangential sliding resistance between the fabric fibers, and the fibers were less likely to move relative to each other; the coating fastens the fibers between the fabrics, increasing the stiffness of the fabric, and the frictional resistance between the fibers increases. 60,61 The findings of the study revealed that the fabrics coated with TiO 2/ gelatin exhibited a favorable ability to recover from wrinkles.…”
Section: Resultsmentioning
confidence: 91%
“…59 Meanwhile, the coating on the surface of the fabric increased the tangential sliding resistance between the fabric fibers, and the fibers were less likely to move relative to each other; the coating fastens the fibers between the fabrics, increasing the stiffness of the fabric, and the frictional resistance between the fibers increases. 60,61 The findings of the study revealed that the fabrics coated with TiO 2/ gelatin exhibited a favorable ability to recover from wrinkles.…”
Section: Resultsmentioning
confidence: 91%